2013
DOI: 10.1111/bcpt.12072
|View full text |Cite
|
Sign up to set email alerts
|

In Utero and Lactational Exposure to Fluoxetine in Wistar Rats: Pregnancy Outcomes and Sexual Development

Abstract: This study evaluated the reproductive effects of fluoxetine exposure in utero and during lactation on pregnancy outcomes and the sexual development of offspring. Pregnant Wistar rats were treated daily with fluoxetine (0.4, 1.7 and 17 mg/kg/ day) or distilled water by gavage from gestation day (GD) 7 to lactation day (LD) 21. A significant reduction in maternal body weight was observed during pregnancy and lactation in dams exposed to 17 mg/kg fluoxetine. Hormone analysis revealed an increase in progestagen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…In the present study we have shown that fetal and neonatal exposure to fluoxetine resulted in a significant increase in body weight in the female but not in the male offspring; these changes occurred in the absence of altered postnatal food consumption despite the fact that fluoxetine has been shown to affect food consumption in adult rodents (Lauzurica et al, 2013). Moreover, although other experiments in rats have reported a reduction in birth weight following fluoxetine exposure during pregnancy (de Oliveira et al, 2013;Müller et al, 2013) we did not observe any effect of fluoxetine in altering birth weight in our study, suggesting that the metabolic deficits in this model are independent of impaired fetal growth. Although the mechanism(s) underlying the sex-specific differences in body composition are unknown, sex-specific differences in the long-term effects of prenatal exposure to SSRIs and childhood overweight have also been reported in human studies (Grzeskowiak et al, 2013).…”
Section: Discussionmentioning
confidence: 40%
“…In the present study we have shown that fetal and neonatal exposure to fluoxetine resulted in a significant increase in body weight in the female but not in the male offspring; these changes occurred in the absence of altered postnatal food consumption despite the fact that fluoxetine has been shown to affect food consumption in adult rodents (Lauzurica et al, 2013). Moreover, although other experiments in rats have reported a reduction in birth weight following fluoxetine exposure during pregnancy (de Oliveira et al, 2013;Müller et al, 2013) we did not observe any effect of fluoxetine in altering birth weight in our study, suggesting that the metabolic deficits in this model are independent of impaired fetal growth. Although the mechanism(s) underlying the sex-specific differences in body composition are unknown, sex-specific differences in the long-term effects of prenatal exposure to SSRIs and childhood overweight have also been reported in human studies (Grzeskowiak et al, 2013).…”
Section: Discussionmentioning
confidence: 40%
“…In one study, exposure to FLX from mid-to-late gestation in rats caused pulmonary hypertension and structural abnormalities of the heart and pulmonary vascular system, coinciding with an increase in postnatal mortality from 0 in controls to 15% in exposed pups [18]. A similar increase was noted by Vorhees et al [19] following prenatal exposure, and by Müller et al [20] following administration of a high dose of FLX to the dam from 1 week after conception to weaning, though lower doses did not have the same effect. In neither study was the cause of this increased mortality examined.…”
Section: Teratogenic and Early Developmental Effectsmentioning
confidence: 58%
“…Finally, sexual differentiation during early life may also be altered, as postnatally exposed male (but not female) rats were found to have shorter than normal anogenital distances at 3 weeks of age, though serum testosterone was not altered, and the difference in anogenital distance was no longer apparent by adulthood in males [26]. In another study, prenatal exposure to low and high doses of FLX was found to have no effect on anogenital distance at birth [20]. …”
Section: Teratogenic and Early Developmental Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found mixed results, with reduced weight: at birth, but not at pre-weaning and during adulthood [42]; at pre-weaning, but not at the juvenile stage [49]; and at pre-weaning, but no difference at the juvenile stage and adulthood [42,47]. Perinatal SSRIs studies have also revealed sex differences at adulthood with reduced weight in males compared to control males (no difference in females; 44; 45, 85] and another study found reduced weights at different time points for males and female rodents (see Table 1 for details) [87].…”
Section: Animal Studiesmentioning
confidence: 93%